Detection of Chlamydia Pneumoniae in Lung Tissues Derived from Lung Tumor-Bearing Iraqi Patients - Lateef, Zainab M.; Melconian, Alice K.; Salman, Ehab D. (Iraqi Journal of Science, 2021)
Chlamydia pneumoniae is an intracellular gram-negative bacteria associated with lower and upper respiratory tract infections. Several studies, mostly achieved by serological assays, proposed a role for this bacteria in lung cancer risk. Therefore, this study aimed to evaluate the prevalence of Chlamydia pneuomoniae in fresh lung tissues of a sample of Iraqi patients with lung tumors, utilizing polymerase chain reaction (PCR) technique. . Chlamydia pneumoniae DNA was detected in 86.67% of samples. Besides, DNA sequencing of 16S rRNA gene revealed that our isolate is closely related to Chlamydia pneumoniae TW183 strain. It is concluded that Chlamydia pneumoniae is found in fresh lung tissues of patients, suggesting past infection, reinfection, or persistent form, which may play a role in the development or exacerbation of lung tumors. Our results confirm the high prevalence of this type of bacteria in Iraqi patients.